Ramananda Chatterjee : selected writings & tributes : birth centenary commemoration volume - Chatterjee, Ramananda, 1865-1943 (Benson's Calcutta, on behalf of Press Institute of India, 1979)
Commemoration volume for an Indian journalist and litterateur.